Cuando la planta habla al botánico – Avances y contratiempos en la decolonización de la educación desde los 1980s: Una entrevista con Gabina Aurora Pérez Jiménez - Gunsenheimer, Antje; Pérez Jiménez, Gabina Aurora; Antillón Sáenz, René (Notas de Antropología de las Américas, 2025)
Interview with political-cultural activist Gabina Aurora Pérez Jiménez, daughter of the Ñuu Sau (“Nation of the Rain”, also known as the Mixtec People; from the state of Oaxaca, Mexico) on the aspects of internal colonialism, the lack of interpretative sovereignty over cultural practices among indigenous communities, educational reforms and resilience against the constant disdain that indigenous peoples receive to this day in Mexico.